Ostracism Increases Automatic Aggression: The Role of Anger and Forgiveness - Zhang, Denghao; Li, Sen; Shao, Lei; Hales, Andrew H.; Williams, Kipling D.; Teng, Fei (Frontiers in Psychology, 2019)
While research on the “ostracism-aggression” link has focused on controlled processes in aggression, little effort has been devoted to examining the relation between ostracism and automatic aggression. Based on theories of aggression, we found that ostracized participants reported higher levels of automatic aggression than included participants (Studies 1 and 2). Furthermore, the association between ostracism and automatic aggression was mediated by anger and was especially prominent for people low in forgiveness (as compared to people high in forgiveness; Study 3). The implications of these findings are discussed.